Revisiting the surface characteristics of fly ash-teff straw ash-based geopolymer mortars in the context of fractal theory - Tajebe Bezabih; David Sinkhonde; Derrick Mirindi (Results in Surfaces and Interfaces)
The popularity of fractal analysis studies is increasing in various fields. However, the literature has neglected the fractal analysis of fly ash (FA)-teff straw ash (TSA)-based geopolymer mortars. This fact inspires us to develop fractal analysis formulations for FA-TSA-based geopolymer mortars that are effective and suitable for characterising several solid specimens. In this study, cube counting, triangulation, power spectrum and partitioning algorithms are proposed to predict the random surfaces of FA-TSA-based geopolymer mortars. The study demonstrates that the partitioning algorithm exhibits the highest fractal dimension values of greater than 2.72 for all the specimens, but yields the lowest coefficients of determination ranging from 0.55 to 0.80. The cube counting, triangulation and power spectrum algorithms achieve coefficients of determination greater than 0.84 in predicting the logarithmic data points. The study also reveals that an increment in the coefficient of determination does not necessarily correspond to higher fractal dimension values. These findings on fractal analysis of FA-TSA-based geopolymer mortars are expected to drive the development of more surface properties of civil engineering materials apart from the conventional roughness parameters. Our current achievements and findings will hopefully pave the way for future studies on the surface properties of other civil engineering materials.